Balance, gait and dizziness in adult cochlear implant users: A cross sectional study. (2nd January 2020) - Murray, Deirdre; Viani, Laura; Garvan, James; Murphy, Alexandra; Vance, Roisin; Simoes-Franklin, Cristina; Smith, Jacyln; Meldrum, Dara
Abstract : Objective: Cochlear implantation is associated with vestibular impairment due to the close proximity of the structures. The aim of the study was to quantify dizziness/vertigo, gaze instability, balance and gait problems in a sample of adult cochlear implant (CI) users. Methods: An observational, cross sectional study evaluated subjective dizziness (Vestibular Rehabilitation Benefit Questionnaire (VRBQ)), balance confidence (Activities Specific Balance Questionnaire (ABC)), gait (Functional Gait Assessment (FGA) and 10m walk test), balance (Equitest Sensory Organisation Test (SOT)), and computerised dynamic visual acuity (DVA). The Dix Hallpike test was performed to test for benign paroxysmal positional vertigo (BPPV). Results: Twenty participants (n=10F), 2.8(±2.7) years post implantation, with mean age 59.3(±15.8) years were assessed. Subjective dizziness (VRBQ) was low (15.0% (±15.5)) and balance confidence was high (ABC: 82.1%±14.9). FGA scores (25.1 ± 4.4) and gait speed (1.8 (±0.3) m/sec) were below normal. Dx Hallpike was positive in 3. Gaze instability was found in 50% (DVA loss, 0.29 (± 0.16) LogMAR), while 79% demonstrated balance impairment (mean SOT score, 57.8%±14.5), with 42% falling on SOT condition 5. Discussion: Evidence of vestibular dysfunction was identified in these adult CI users. Conclusion: Access to vestibular function assessment and rehabilitation is required in adult CI users.